POPE FRANCIS AND INCULTURATION - Stephen Bevans (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: This article contains the idea of Pope Francis’ contextualizations as expressed in some of his encyclicals. In his Evangelii Gaudium (Joy of the Gospel), Pope Francis supports inculturation as well as having the view that Hellenist culture is particularly appropriate in expressing Christian faith, and thus needs to be appreciated as a norm for the Church aside from the Holy Bible. In his Laudato Si (On Care for our Common Home), Pope Francis refers to a method used in liberation theology that is “See – judge – act”. Pope Francis stresses the importance of the process of observation of situations, considering the causes, and designing the actions. By referring to chapter 8 of the Apostolic Mandate Amoris Laetitia (The Joy of Love), the risks that must always be carried by each person who wishes to confront the Gospel with concrete-actual conditions are discussed. In the concluding part of this article several examples of the Pope’s sensitivity towards cultures and unusual and complex social political situations are shown by referring to the Magnum Principium (The Great Principle) Decree and the visit of Pope Francis to Myanmar.Keywords: Pope Francis, Evangelii Gaudium, Laudato Si’, Amoris Laetitia, Magnum Principium, theology inculturation